Critical Feature and Seawater Testing of Cross-Flow Rotor Components Fabricated with Additive Manufacturing (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Cross-flow tidal turbines are an attractive option for powering remote or off-grid applications because of their simplicity as compared to axial-flow turbines. For instance, when oriented vertically, they harvest power from any current direction with a single degree of freedom and no yaw mechanism. Additive manufacturing (AM) offers an opportunity to print parts out of a wide variety of materials that can result in components that are lighter, stronger and/or less expensive to produce than with traditional manufacturing techniques. When coupled with cross-flow turbine rotors, which require critical features (blade-strut, strut-shaft connections) to be both structurally stiff and hydrodynamically shaped, which can be challenging for typical fabrication processes, AM offers the ability to do both well. This paper describes work on the feasibility of using advanced AM techniques to fabricate small cross-flow turbine rotors for applications at sea and near remote coastal communities.AM materials were categorized into 3 classes – plastics, metals, and ceramics – and reviewed for suitability based on a set of engineering requirements and criteria related to turbine characteristics, material properties, and AM process capabilities. Two plastics and two metals were selected to undergo further testing: Essentium CF25, CarbonX Ult 9085, Titanium Ti-6Al-4V, and Inconel 718. Testing is conducted in three phases: the first is a long-term, 5-month submersion test in the seawater tanks at PNNL-Sequim to study corrosion, water uptake, and biofouling potential; in the second, materials are tensile tested on a load frame to find their failure parameters to compare to material standards; the third test is a fatigue test consisting of cyclically loading test parts with a known force on the order of that exerted on rotor blades in a 1.5 m/s current flow. These tests are designed to discern the suitability of AM materials since their properties from 3D printing processes are known to vary from published parameters. The test samples undergoing submersion testing will be tension tested and compared to control samples not subjected to extended seawater immersion. For fatigue life testing, a small rotor is expected to complete 100 million cycles over the course of a year-long lifespan, but for the case herein is restricted to 1 million for a preliminary performance evaluation. The first 10k cycles are run on an MTS 312.21 load frame at a rate of 0.2 Hz, with the remaining on a custom-built cyclic-deflection test rig at 0.8 Hz.